1990
DOI: 10.1152/ajpregu.1990.258.6.r1402
|View full text |Cite
|
Sign up to set email alerts
|

Vascular reactivity of the coronary artery in rainbow trout (Oncorhynchus mykiss)

Abstract: Vascular reactivity of the large coronary artery of a lower vertebrate was investigated for the first time in this study. The responses of vascular rings to various pharmacological agents were measured using isometric force transducers. Coronary arteries from rainbow trout, Oncorhynchus mykiss, contracted with acetylcholine and predominantly relaxed with isoproterenol, epinephrine, norepinephrine, and serotonin. Atenolol blocked the adrenergic relaxation, suggesting a predominance of beta 1-adrenoceptors. Nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 0 publications
9
30
0
Order By: Relevance
“…Higher vasoconstriction to acetylcholine was observed in ABA and EBA in I. conceptionis in comparison with G. laevifrons, and a minor effect of blockade with indomethacine in the maximum response to acetylcholine was observed in ABA and DA vessels in I. conceptionis as compared to G. laevifrons. In general, the results obtained in both of these species are partially in agreement with previous studies performed in species of great phylogenetic distance (agnathes, elasmobranches, teleost), that showed that acetylcholine induced contraction (Small et al, 1990;Miller and Vanhoutte, 1992;Evans and Gunderson, 1998a). However, the Ach-mediated vasoconstriction described in our study suggests that the coupled Ach-COX contraction produced when there is a decreased availability of nitric oxide (NO) is similar to that reported in human hypertension or hypertension models in rats (Vanhoutte et al, 2005;Shi et al, 2008).…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Higher vasoconstriction to acetylcholine was observed in ABA and EBA in I. conceptionis in comparison with G. laevifrons, and a minor effect of blockade with indomethacine in the maximum response to acetylcholine was observed in ABA and DA vessels in I. conceptionis as compared to G. laevifrons. In general, the results obtained in both of these species are partially in agreement with previous studies performed in species of great phylogenetic distance (agnathes, elasmobranches, teleost), that showed that acetylcholine induced contraction (Small et al, 1990;Miller and Vanhoutte, 1992;Evans and Gunderson, 1998a). However, the Ach-mediated vasoconstriction described in our study suggests that the coupled Ach-COX contraction produced when there is a decreased availability of nitric oxide (NO) is similar to that reported in human hypertension or hypertension models in rats (Vanhoutte et al, 2005;Shi et al, 2008).…”
Section: Introductionsupporting
confidence: 91%
“…the same authors describe that this vasoconstriction was abolished by the use of atropine (10 -5 M). This evidence has been corroborated by other studies in trout, shark and eel (Nilsson and Grove, 1974;Pellegrino et al, 2003;Pellegrino et al, 2002;Small et al, 1990), supporting the presence of muscarinic receptors in fish vasculature.…”
Section: Role Of L-name In the Ach-mediated Contractionsupporting
confidence: 82%
See 1 more Smart Citation
“…The vasodilator activity of adenosine in the frog aorta is consistent with its vasodilator action in both mammals (see Burnstock, 1990b) and fish vessels, including the trout and skate coronary arteries (Small et al, 1990;Farrell & Davie, 1991) and dogfish aorta (Meghji & Burnstock, 1984). In mammals the subclass of P1-purinoceptor mediating vasodilatation of most vessels is the A2-receptor (Burnstock, 1990b).…”
Section: Discussionmentioning
confidence: 52%
“…Studies have revealed PI-purinoceptors on the coronary artery of trout and skate (Small et al, 1990;Farrell & Davie, 1991) and trout gill vasculature , dogfish atria and aorta (Meghji & Burnstock, 1984;Evans, 1992). ATP has been shown to dilate the portal vein of the lizard (Ojewole, 1983).…”
Section: Introductionmentioning
confidence: 99%